1993
DOI: 10.1007/bf01789125
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of synthetic peptides related to the core peptide sequence encoded by the human MUC1 mucin gene: Effect of immunization on the growth of murine mammary adenocarcinoma cells transfected with the human MUC1 gene

Abstract: The immune response of CAF1 mice to various synthetic peptides (SP) related to the amino acid sequence (PDTRPAPGSTAPPAHGVTSA) of the tandem repeat of the MUC1 human breast mucin core peptide was evaluated. The most immunogenic preparations of the synthetic peptides were those conjugated to keyhole limpet hemocyanin (KLH) or clustered in a dendritic multiple antigenic peptide (MAP-4) configuration. The mice were immunized subcutaneously with synthetic peptides emulsified in RIBI adjuvant, employing various immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…These data further suggest that the generated sera is minimally binding to normal tissues while displaying strong binding to tumor tissues that over express histoblood group related carbohydrates. These data suggest that even though this serum reacts with common structural features of MCP and LeY, the presentation of related carbohydrate forms on tissues are affected by the carrier molecules to which they are attached as previously suggested (39) or the density of expressed carbohydrate.…”
Section: In Vitro and In Vivo Functionality Of Le Antigen Mimicking Psupporting
confidence: 67%
“…These data further suggest that the generated sera is minimally binding to normal tissues while displaying strong binding to tumor tissues that over express histoblood group related carbohydrates. These data suggest that even though this serum reacts with common structural features of MCP and LeY, the presentation of related carbohydrate forms on tissues are affected by the carrier molecules to which they are attached as previously suggested (39) or the density of expressed carbohydrate.…”
Section: In Vitro and In Vivo Functionality Of Le Antigen Mimicking Psupporting
confidence: 67%
“…Our data are consistent with earlier reports that the PDTRP core epitope of human MUC-1 was immunogenic in mice, and PDTRP-specific immune responses induced with a peptide-based vaccine could delay tumor growth. Ding et al 45 demonstrated that peptide-based PDTRP vaccination with a proper adjuvant or Th epitope could induce strong PDTRP-specific antibody and DTH responses, which correlated directly with prolonged survival of tumor-bearing mice. Using a DNA vaccine approach, Kontani et al 46 showed that a MUC-1-based DNA vaccine induced a protective antitumor immunity in naı¨ve mice, but the efficacy of the DNA vaccine in tumorbearing mice strictly depended on the induction of cellmediated immune responses and coinjection of activated DCs.…”
Section: Discussionmentioning
confidence: 99%
“…They exhibit unique glycosylation patterns, making them tumor-specific immunogens. 34 In a phase I clinical trial using MUC1 peptide in stage III/IV NSCLC, 35 safety and tolerability of this agent was established. Five of 12 patients (42%) had immunologic responses, and 4 of 12 patients (33%) achieved stable disease.…”
Section: Antigen-specific Vaccinationmentioning
confidence: 99%